Implementation of an outbreak response vaccination campaign with typhoid conjugate vaccine – Harare, Zimbabwe, 2019. (December 2022) - Poncin, M.; Marembo, J.; Chitando, P.; Sreenivasan, N.; Makwara, I.; Machekanyanga, Z.; Nyabyenda, W.; Mukeredzi, I.; Munyanyi, M.; Hidle, A.; Chingwena, F.; Chigwena, C.; et al.
Abstract: Introduction: Typhoid fever is a public-health problem in Harare, the capital city of Zimbabwe, with seasonal outbreaks occurring annually since 2010. In 2019, the Ministry of Health and Child Care (MOHCC) organized the first typhoid conjugate vaccination campaign in Africa in response to a recurring typhoid outbreak in a large urban setting. Method: As part of a larger public health response to a typhoid fever outbreak in Harare, Gavi approved in September 2018 a MOHCC request for 340, 000 doses of recently prequalified Typbar-TCV to implement a mass vaccination campaign. To select areas for the campaign, typhoid fever surveillance data from January 2016 until June 2018 was reviewed. We collected and analyzed information from the MOHCC and its partners to describe the vaccination campaign planning, implementation, feasibility, administrative coverage and financial costs. Results: The campaign was conducted in nine high-density suburbs of Harare over eight days in February–March 2019 and targeted all children aged 6 months–15 years; however, the target age range was extended up to 45 years in one suburb due to the past high attack rate among adults. A total of 318, 698 people were vaccinated, resulting in overall administrative coverage of 85.4 percent. More than 750 community volunteers and personnel from the MOHCC and the Ministry of Education were trained and involved in social mobilization and vaccination activities. The MOHCC used a combination of vaccination strategies (i.e., fixed and mobile immunization sites, a creche and school-based strategy, and door-to-door activities). Financial costs were estimated at US$ 2.39 per dose, including the vaccine and vaccination supplies (US$ 0.79 operational costs per dose excluding vaccine and vaccination supplies). Conclusion: A mass targeted campaign in densely populated urban areas in Harare, using the recently prequalified typhoid conjugate vaccine, was feasible and achieved a high overall coverage in a short period of time.